Penerapan Human Relations PT Manajemen Qolbu questrian Dalam Membina Hubungan Kerja Yang Harmonis - Puspitha, Mita; Suherdiana, Dadan; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
Employees in a work environment have different backgrounds, so there are complex communication dynamics. Human relations is present as a communication lubricant through the concePT of ethical communication which is oriented towards the inner life of employees. This research aims to describe the input stage of company human relations in the form of work facilities, the process stage in the form of internal program management by public relations and the output stage of harmonization of work relations. The categorization reference is based on Elton Mayo's theory of human relations. This research uses a constructivist paradigm with in-dePTh interview data collection techniques which are studied based on descriPTive analysis methods. This research produces a categorization of the input, process and output stages of PT Management Qolbu Equestrian's human relations which indicates harmonization of relationships based on spiritual values.